Caesarean section: an epidemic - Uppadhaya, Sandeep Kumar; Verma, Manoj (International Journal Of Community Medicine And Public Health, 2018)
Worldwide steady increase in caesarean section (CS) rate during the last decades has been the cause of alarm and needs an in depth study. Caesarean section is major surgery and increases the likelihood of many short and longer-term adverse effects in mothers and babies. The caesarean epidemic is a reason for immediate concern and deserves serious international attention. There are to be needs to make policy on caesarean section for reversing this trend that can be truly called as "Caesarean section: an epidemic”.